Analisis kualitas pelayanan izin usaha pada dinas penanaman modal dan pelayanan terpadu satu pintu kabupaten sikka - Victoria, Prima (Jurnal Ilmiah Cakrawarti, 2023)
Public service currently has several different views judged from a variety of perspectives. Some day the service is not in accordance with the expectations of the community, but there are also those who say that thw services provided are ini accordance with what the community wants. For this reason, this study aims to determine the quality of bussines permit service at the investment service and one-stop integrated ervice in Sikka Regency. This research is a descriptive qualitative focuses on the dimensions of the quality of public services according to zeithmal, parasuraman and berry in hardiansyah that dimension is reliability, responsiveness,assurance, of empati and tangibels. Sources of data and results or information in this study must be chosen based on purposive sampling techniques. The data validity checking technique used in this study is triangulation. In data analysis techniques in this study, namely the reduction of data presentation of data and drawing conclusion. From the results of research on the quality of business permit services in the investment services and one stop integrated services in Sikka Regency with the five dimensions mentioned above, it can be seen that the five dimensions have been implemented well although there are still shortages or obstacles that are not too visible.